Pain Sensitivity Mediates The Relationship between Stress and Headache Intensity in Chronic Tension-Type Headache - Stuart Cathcart; Navjot Bhullar; Maarten Immink; Chris Della Vedova; John Hayball (Pain Research and Management)
BACKGROUND: A central model for chronic tension-type headache (CTH) posits that stress contributes to headache, in part, by aggravating existing hyperalgesia in CTH sufferers. The prediction from this model that pain sensitivity mediates the relationship between stress and headache activity has not yet been examined.